(untitled) (Journal of Pharmaceutical Negative Results, 2023)
This study aimed to assess the histopathological efficacy of Nigella sativa (N. Sativa) oil to prevent 5-fluorouracil (5-FU)-induced mucositis in rats. In this animal study, mucositis was induced in 96 albino Wistar rats by injection of 5-FU. The rats were then randomly divided into three groups: control, placebo, and pre-treatment with N. Sativa. The rats in the third group received 100 mg/kg N. sativa on day 1 and 65 mg/kg on day 3. The / buccal mucosa of all rats was scratched with an 18-gauge needle at 3 and 5 days. Groups 2 (placebo) and 3 (pre-treatment) received 400 µL kg/day placebo and N. Sativa oil intraperitoneally respectively daily, starting from 15 days prior to chemotherapy until the last day of the experiment. Biopsy specimens were obtained from the buccal mucosa of 8 rats in each group at 3, 6, 9 and 12 days for histopathological analysis. The severity of mucositis was evaluated by measuring three parameters namely epithelial changes, level of inflammation (based on the percentage of inflammatory cells present) and connective tissue changes. Data were analyzed using the Kruskal-Wallis and Mann-Whitney tests. The severity of mucositis in the pre-treatment group was significantly lower than that in the placebo and control groups at 3 (P=0.010) and 6 (P=0.012) days; however, this difference was not significant at other time points (P>0.05). Intraperitoneal injection of N. Sativa oil can decrease the severity of 5-FU-induced mucositis in rats.